2020
DOI: 10.3390/molecules25184241
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of a High Sensitivity LC-MS/MS Method for the Determination of Hesperidin and Naringenin in Rat Plasma: Pharmacokinetic Approach

Abstract: The purpose of this study was to develop, optimize, and fully validate a high-sensitivity methodology using UHPLC-MS/MS to simultaneously quantify hesperidin and naringenin in microsamples (100 µL) of murine plasma after intragastric administration of single pure flavonoids and a mixture. The optimization process allowed for high sensitivity with detection limits of approximately picogram order using an electrospray ionization (ESI) source in negative mode and an experiment based on multiple reaction monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…According to international guidelines, recovery intervals are between 60% to 115%, with a precision of 21% to 32% [9,10]. Results showed that previous evidence reported by Araujo-León et al [8] showed a precision lower than 10% and an excellent recovery of more than 90% in picograms concentration order. This was compared to our results with research with flavonoids with a similar chemical structure that were evaluated in rat serum samples analyzed by LC-MS/MS.…”
Section: Quality Controlmentioning
confidence: 54%
See 1 more Smart Citation
“…According to international guidelines, recovery intervals are between 60% to 115%, with a precision of 21% to 32% [9,10]. Results showed that previous evidence reported by Araujo-León et al [8] showed a precision lower than 10% and an excellent recovery of more than 90% in picograms concentration order. This was compared to our results with research with flavonoids with a similar chemical structure that were evaluated in rat serum samples analyzed by LC-MS/MS.…”
Section: Quality Controlmentioning
confidence: 54%
“…Then, we evaluated the pharmacokinetic of the tablet in comparison with the mixture (Mix-160). For this, a prevalidated and optimized analytical methodology was used by a LC-MS/MS system for quantifying analytes in rodent plasma samples [8]. Our results allowed us to establish the pharmacokinetic basis for extrapolating in clinical trials those that assess the efficacy and safety of a citroflavonoid-based drug for the treatment of diabetes and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…29 According to our current study, the CL/Fz data of atractylenolide III, ferulic acid and geniposide were not more than 500 mL h −1 kg −1 , while the CL/Fz data of hesperidin, naringin and puerarin were more than 90 000 mL h −1 kg −1 . Compared with the literature, 28,30–34 the results indicate that some metabolic enzymes in the depressed rats were activated by acute stress, while some were inhibited, highlighting the value of studying the metabolism of depression in vivo and in vitro . Thus, our future research will focus on the metabolism of XYSJW and compatibility mechanism using depressed rats and rat liver microsomes.…”
Section: Resultsmentioning
confidence: 79%
“…"Liquid chromatography tandem mass spectrometry (LC-MS)" assay has also been established for the determination of HSP in combination with other bioflavonoids in its plant-based materials [20]. Various LC-MS-based assays were also applied for the determination of HSP in combination with other bioflavonoids in the biological fluids of rats and humans [21][22][23][24][25]. An "ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS)" method has also been established for the simultaneous analysis of HSP, neo-HSP, naringin, naringenin, meranzin hydrate, and hesperitin in rat plasma samples and plant extract [26].…”
Section: Introductionmentioning
confidence: 99%
“…In reported LC-MS and UPLC-MS methods of HSP analysis, the mobile phase used was the binary combination of acetonitrile-W or acetonitrile-buffers. Acetonitrile is a highly toxic solvent and hence reported LC-MS and UPLC-MS methods are not safe and sustainable for HSP analysis [20][21][22][23][24][25][26]. A fluorimetry method has also been established for the simultaneous estimation of HSP and diosmin in combined dosage form and human plasma samples via complex formation using terbium [27].…”
Section: Introductionmentioning
confidence: 99%